Psychological Impact of COVID Pandemic among the Armed Forces Healthcare Workers (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: The 2019 novel corona virus (COVID-19) pandemic is an international public health emergency unprecedented in modern history. Hospitals had to rapidly reconﬁgure clinical spaces and restructure clinical teams to address the surge of patients with COVID-19. The unique situation might have psychological impact such as stress, anxiety, depressive symptoms, insomnia, denial and fear among the military health care workers.Objective: To assess the psychological impact of COVID-19 on army healthcare workers at the designated COVID Hospital in Sylhet cantonment.Methods: A total of 160 participants were selected using convenience sampling from 01 May 2020 to 31 August 2020. The psychological impact was assessed by Impact of Event Scale-Revised (IES-R) adopted from Horowitz 1979. The 22-item scale comprised of 3 subscales representative of the major symptom clusters of post-traumatic stress: intrusion, avoidance and hyper-arousal. Stress for job, financial issue, home and feeling horrified or helpless due to the COVID-19 were also assessed.Results: Majority (46.3%) of the participants were revealed with mild psychological impact. Moderate and severe impact was found among 18.8% and 7.5% respondents respectively. Mean stress (0-88) was observed as 27.79±6.94. Mean intrusion (27.21±10.924) and Hyper-arousal (19.57±8.130) depicted mild to moderate but Avoidance (34.53±11.072) revealed relatively high level of stress. Majority were not at all stressed for financial issue (49.4%) or for their job (46.3%). But stress for family (20%), feeling horrified (31.9%) and helpless (31.9%) was moderate.Conclusion: The study observed mild to moderate psychological impact among the respondents. A considerable proportion was found to have severe psychological impact which demands appropriate intervention.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 35-39